Psychological empowerment and job satisfaction in nurses: A systematic review and meta-analysis - Gu, Lihua; Wang, Liping; Pan, Biwei (Frontiers in Public Health, 2022)
Background Psychological empowerment is generally understood to be associated with job satisfaction among nurses. However, recently published literature has questioned this association. Objective We aimed to systematically investigate through a meta-analysis the association of psychological empowerment with job satisfaction among nurses. Methods PubMed, Medline, Cochrane Library, PsycInfo, and Embase were used to search targeted studies from conception to 20 January 2022. The correlation coefficients of each study were extracted and converted into Fisher's Z. Finally, pooled r was calculated by Fisher's Z and standard error (SE). Results A total of 28 studies encompassing 27 articles with 7,664 registered nurses were included. The pooled correlation coefficient between psychological empowerment and job satisfaction was 0.55. Subgroup analyses were conducted according to ethnicity, and the correlation in the Asian participants (P < 0.01) was significantly stronger (P < 0.05) than that of the Caucasian nurses (P < 0.01). Conclusions Psychological empowerment is strongly correlated to job satisfaction for registered nurses, especially among those from Asian countries. Interventions designed for psychological empowerment could be one of the strategies to promote the retention of nurses. Nonetheless, additional future studies are essential for more investigations.